Governança corporativa e o papel estratégico do conselho de administração - Sartori, Gisele (My University, 2022)
A Board focused on the present and strategic thinking for the future is fundamental to good corporate governance practices. Although board involvement in strategy is increasingly important, understanding how boards play this role can still be more fully studied. The objective of this dissertation is to understand the Board involvement on strategy formulation in family organizations in Serra Gaúcha. This study is characterized by its nature as applied, and its purpose as exploratory. The research is a mixed method, and was made through a converging parallel project, with application of two forms aimed at the attributes of the board member (integrity, competence and constructive involvement), and the board's involvement in the strategic perspective. Semi-structured interviews were carried out with nine members who work in seven Boards of family businesses and observations in board meetings. The results indicate that the individual attributes of the board member guides the Board towards greater involvement in the formulation of the strategy, thus exposing a perspective that goes from the individual to the collective. The board structure guides the degree of involvement in strategy formulation, the intention to act in this perspective was observed as a latent characteristic. [resumo fornecido pelo autor]
Um Conselho de Administração com o olhar no presente e o pensamento estratégico voltado para o futuro é fundamental para as boas práticas de governança corporativa. Embora o envolvimento do conselho na estratégia seja cada vez mais importante, a compreensão de como os conselhos exercem esse papel ainda pode ser mais amplamente estudada. O objetivo desta dissertação é de compreender o envolvimento do Conselho de Administração na formulação da estratégia em organizações familiares da Serra Gaúcha. Este estudo se caracteriza quanto à sua natureza como aplicado, quanto a finalidade como exploratório. A pesquisa é de método misto, e foi viabilizada por meio de um projeto paralelo convergente, com aplicação de dois formulários voltados aos atributos do conselheiro (integridade, competência e envolvimento construtivo), e ao envolvimento do conselho na perspectiva estratégica. Foram realizadas entrevistas semiestruturadas com nove conselheiros que atuam em sete Conselhos de Administração de empresas familiares e observações em reuniões de conselho. Os resultados indicam que os atributos individuais do conselheiro direcionam o Conselho de administração para um maior envolvimento na formulação da estratégia, expondo, portanto, uma perspectiva que parte do individual para o coletivo. A estrutura do conselho direciona o grau de envolvimento na elaboração da estratégia e observou-se como característica latente a intenção de atuar nesta perspectiva. [resumo fornecido pelo autor]
Keywords: Governança corporativa; Administração de empresas; Planejamento estratégico; Corporate governance; Industrial management; Strategic planning